Youth’s Depression of an Artist Portrayed in “Lonely”Song by Justin Bieber - Mursalim, Mufida Julia; Mustikawati, Yunitari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
The aims of this study are to analyze the messages in the song